The “Information Paradox” in crime prevention: how spatial context and age moderate the impact of safety advisories on residents’ perception of safety - Zengli Wang (Frontiers in Public Health, 2026)
Background Effective crime prevention communication is a cornerstone of urban public health and psychological well-being. However, the psychological impact of safety advisories on residents remains poorly understood. This study investigates the “Information Paradox,” the phenomenon where crime prevention tips may inadvertently heighten fear rather than provide reassurance, and explores how spatial delivery channels and demographic factors moderate this relationship. Methods Drawing on a survey of residents in Nanjing, China, this study employed ordinal logistic regression (OLR) models to analyze the influence of multi-channel information (e.g., Community Noticeboards, unit entrances, elevator lobbies, and digital platforms) on perceived safety. Interaction terms were introduced to examine the moderating role of age cohorts, shifting the focus from technological access to varying risk sensitivities and socio-economic responsibilities across life stages. Results The results reveal a significant spatial divergence in information perception. Crime prevention tips at unit entrances significantly enhance safety perceptions ( B = 0.370, p < 0.05), acting as signs of guardianship. Conversely, reminders in elevator lobbies correspond to a sharp decline in security feelings ( B = −0.741, p < 0.01) triggering a micro-spatial warning effect where structural entrapment overrides message intent. Furthermore, interaction analysis shows that the early-to-middle-aged groups exhibit a systematically lower likelihood of high safety alignment. Notably, the interaction terms for (31–40 year) × Television News ( B = −1.985, p = 0.002, OR = 0.137) and (41–50 years) × Mobile Applications ( B = −1.556, p = 0.026, OR = 0.211) act as strong negative deflators against the senior baseline (>50 years). Overall, are most sensitive to risk salience, experiencing a sharp decline in safety perception when exposed to Television News and Mobile Applications. Overall, place-based offline channels exert a more continuous psychological weight than decentralized digital notifications due to their material embodiment and proximity to daily routines. Conclusion The psychological efficacy of crime prevention information is highly context-dependent and spatially bounded. To foster a secure urban environment, city managers must transition from “one-size-fits-all” public broadcasting toward demographically tailored and spatially synchronized communication architectures. Prioritizing reassurance at territorial thresholds while boosting actionable self-efficacy for middle-aged caregiving cohorts can successfully mitigate unintended environmental anxiety and maximize the public health dividends of smart-community governance.